Pelatihan Pembuatan Atap Tradisional dari Daun Serule di Desa Genuren, Kecamatan Bintang, Kabupaten Aceh Tengah - Sari, Laina Hilma; Agustina, Sylvia; Djamaluddin, Masdar; Wulandari, Elysa (Universitas Syiah Kuala, 2024)
In tourism development, the majority of building materials used are modern materials. Even many local people are not familiar with the typical building materials of Central Aceh. Roofs made of serule leaves are traditional materials in Central Aceh (Ferah Yosantia et al., n.d.). The serule plant has flowers and leaves that are similar to Etlingera elatior, the Zingiberaceae family. Serule leaves grow abundantly around the edge of Lake Laut Tawar, Bintang District which continues eastward for 20 km to Serule Village. So this community service developed the manufacture of serule leaf roofs through mentoring and training for the people of Genuruen Village. This service activity was carried out in Genuren Village, Aceh Tengah applying several stages, namely: preparation stage, socialization, and implementation of activities and evaluation. Each stage is carefully planned so that the activity runs according to expectations. There are several parties involved in this activity. The results of this training will be used as a roof covering material for Umah Pitu Ruang, as a continuation of the unfinished UPR Redevelopment project. The goal is to maintain and revive the tradition of traditional craftsmanship. In addition, the final product of this serule soup will also be used in the renovation of gazebos as public facilities in Genuren Village. From the training activities on making traditional roofs using serule leaves, the community gained knowledge and skills to make serule soup. Thus, the community in Genuren Village can preserve the serule plant which is now rare, utilize local resources effectively, and improve their economic welfare.